Biomarkers of oxidative stress and health risk assessment of heavy metal contaminated aquatic and terrestrial organisms by oil extraction industry in Ogale, Nigeria. (October 2017) - Abarikwu, Sunny O.; Essien, Eka B.; Iyede, Oreva-Oghene; John, Kingsley; Mgbudom-Okah, Chidimma
Abstract: Ogale community in Rivers State, Nigeria is characterized by crude-oil contamination of its land resources. The present study aimed to evaluate the health risk and metal (Cd, Pb, Zn, Cr, and Ni) contamination level of the vegetable ( Telfairia occidentalis ), snail ( Achatina achatina ) and the catfish ( Clarias gariepinus ) collected from Ogale community. Samples collected from Elele Alimini community, a less polluted area was used as control. Oxidative damage was evaluated in tissues of snail and in the liver of catfish. The concentration of most of the tested metals in the food samples collected from the polluted sites were higher than those from the reference sites and in most cases exceeded the acceptable permissible limits. The accumulation of the metals by the food samples followed the order: T. occidentalis  >  A. achatina  >  C. gariepinus. The tissues of the snail from the polluted sites showed higher malondialdehyde (MDA) and lower glutathione (GSH) levels, and higher MDA and GSH levels in the fish liver compared to control values. The health risks associated with these metals in terms of dietary intake and target hazard quotients (THQs) showed higher non-carcinogenic effect and carcinogenic risks especially for Pb and Cd from the ingestion of Telfairia occidentalis and Achatina achatina from polluted sites. The health hazards due to metal pollution for the highly-exposed consumers of the food samples, especially in Ogale require attention. The oxidative stress response to accumulation status of metals provides a relevant tool for the assessment of metal pollution. Highlights: Heavy metals were detected in contaminated food samples in Ogale, Nigeria. High concentration of metals were detected in the vegetable, T. occidentalis . Least concentration of metals were detected in the catfish, C. gariepinus . Applying dietary intake and health risk calculation is proposed. Pb is the only metal through vegetable consumption that posed potential health risk.